Abnormal Paraventricular Nucleus of Hypothalamus and Growth Retardation Associated with Loss of Nuclear Receptor Gene COUP-TFII - Su Feng (Nature Portfolio, 2017)
Abstract The paraventricular nucleus of hypothalamus plays important roles in the regulation of energy balance and fetal growth. However, the molecular mechanisms underlying its formation and function have not been clearly elucidated. Various mutations in the human COUP-TFII gene, which encodes a nuclear receptor, result in growth retardation, congenital diaphragmatic hernia and congenital heart defects. Here, we show that COUP-TFII gene is expressed in the developing hypothalamus in mouse. The ventral forebrain-specific RXCre/+; COUP-TFII F/F mutant mice display growth retardation. The development of the paraventricular nucleus of hypothalamus is compromised in the COUP-TFII mutant mainly because of increased apoptosis and mis-migration of the Brn2+ neurons. Moreover, hypoplastic anterior pituitary with blood cell clusters and shrunken posterior pituitary lacking AVP/OT neuron innervations are observed in the mutant, indicating the failure of formation of the hypothalamic-pituitary axis. Mechanistic studies show that the expression of Bdnf and Nrp1 genes is reduced in the mutant embryo, and that Bdnf is a direct downstream target of the COUP-TFII protein. Thus, our findings provide a novel functional validation that COUP-TFII gene promotes the expression of Bdnf and Nrp1 genes to ensure the appropriate morphogenesis of the hypothalamic-pituitary axis, especially the paraventricular nucleus of hypothalamus, and to prevent growth retardation.